2021
DOI: 10.7759/cureus.14897
|View full text |Cite
|
Sign up to set email alerts
|

Aggressive Hydration With Ringer's Lactate in the Prevention of Post-ERCP Pancreatitis: A Meta-Analysis

Abstract: Post-endoscopic retrograde cholangiopancreatography (ERCP) pancreatitis (PEP) is a dangerous complication and occurs in a considerable number of patients. However, since well-randomized controlled trials investigating aggressive hydration with Ringer's lactate are lacking, this meta-analysis assessed the role of aggressive hydration with Ringer's lactate alone or in combination with other therapies in the prevention of PEP. We searched PubMed, Cochrane Library, and Google Scholar for relevant articl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 24 publications
(31 reference statements)
0
1
0
Order By: Relevance
“…Studies have shown that the incidence of PEP ranges from 1% to 24%, and death may by caused by severe PEP, posing a great medical burden. Therefore, it is a research hotspot to increase the safety of ERCP and avoid PEP [5][6][7]. Pharmacological interventions are an important tool to prevent PEP.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that the incidence of PEP ranges from 1% to 24%, and death may by caused by severe PEP, posing a great medical burden. Therefore, it is a research hotspot to increase the safety of ERCP and avoid PEP [5][6][7]. Pharmacological interventions are an important tool to prevent PEP.…”
Section: Introductionmentioning
confidence: 99%